Diels-Alder/Oxidative Aromatization Approach towards the All-Carbon DEF Tricyclic Skeleton of Daphenylline - Li, Huilin; Qiu, Yangcheng; Zhao, Changgui; Yuan, Ziyun; Xie, Xingang; She, Xuegong (Chemistry, an Asian journal, 2014)
Daphenylline is a recently isolated Daphniphyllum alkaloid with an unprecedented novel hexacyclic scaffold. In this study, the synthesis of the fused all‐carbon DEF tricyclic skeleton of daphenylline has been accomplished. Key steps of the reported sequence involve Evans asymmetric allylation, aldol condensation, Diels–Alder reaction, and oxidative aromatization reactions. The developed strategy might lead to the total synthesis of daphenylline. DEF‐initely maybe: Synthesis of the fused all‐carbon DEF tricyclic skeleton of daphenylline, a structurally novel Daphniphyllum alkaloid, has been accomplished based on a Diels–Alder/oxidative aromatization strategy. The finished approach, in combination with our previous research for the construction of the ABC ring system, may lead to the asymmetric total synthesis of daphenylline.